HUBUNGAN STOK KARBON TANAH DAN SUHU PERMUKAAN PADA BEBERAPA PENGGUNAAN LAHAN DI NAGARI PADANG LAWEH KABUPATEN SIJUNJUNG - Gunadi Gunadi; Juniarti Juniarti; Gusnidar Gusnidar (Jurnal Solum, 2020)
The content of soil C-organic is strongly influenced by land management. Plants tend to increase soil organic C-stock, however an increase in soil temperature can increase the rate of decomposition of soil organic matter which will reduce soil organic C-stock. The aim of the study is to look at the relationship of soil organic carbon stock (SOCS) with changes in soil surface temperature. The study was conducted using a survey method consisting of 5 stages, namely preparation, pre-survey, main survey, soil analysis in the laboratory and data processing. Soil sampling is done by purposive random sampling under several land units (LU). LU is limited by the order of the soil, slope, and land use. Based on the land unit map, we found 14 land units in the study area. Soil samples were taken at a depth of 0-20 cm. Surface temperature measurements are carried out directly in the field using a room temperature thermometer. The parameters analyzed are organic-C, organic particulate-C, and bulk density (BD). The research data were processed statistically using simple linear regression equations. The results showed that the measurement of rice field surface temperature had the highest temperature of 34 0C, and rubber plantations had the lowest temperature of 28 0C. Organic-C affects soil BD, the higher the value of organic-C, the lower the BD value. The highest carbon stock was found in soil unit 10 with rubber plantations with a slope of 8-15%, 41 kg m-2 and decreased with increasing slope. The difference in the value of SOCS in rice fields is influenced by land management, because there is no return of crops residue in the form of straw to the ground. The results of the regression analysis showed that surface temperature did not have a significant effect on the SOCS value.Keywords : carbon stock, land use, Padang Laweh